What the dinosaurs did the night before Christmas - Tuma, Refe; Tuma, Susan (New York : Little, Brown and Company, 2021)
"In this reimagining of the classic 'Twas the Night Before Christmas, the dinosaurs of Dinovember are up to all kinds of holiday mischief!"--
Ages 4-8.
109339
Keywords: Dinosaurs -- Juvenile fiction; Christmas stories; Stories in rhyme; Behavior; Humorous fiction; Juvenile works; Children's stories -- Pictorial works